Is the mind a cauliflower or an onion? British insights into cognitive organization from the study of abnormal function. - McCarthy, Rosaleen A. (British Journal of Psychology, 2001)
Clinical and normal psychology have had a long tradition of close interaction in British psychology. The roots of this interplay may predate the development of the British Psychological Society, but the Society has encouraged and supported this line of research since its inception. One fundamental British insight has been to consider the evidence from pathology as a potential constraint on theories of normal function. In turn, theories of normal function have been used to understand and illuminate cognitive pathology. This review discusses some of the areas in which clinical contributions to cognitive theory have been most substantial. As with other contributions to this volume, attempts are also made to read the runes and anticipate future developments. Reprinted by permission of the publisher.